Investigation of electromagnetic fields in the arctic zone with uneven ice cover - Korochentsev Vladimir (EDP Sciences, 2021)
Numerical investigation of electromagnetic waves propagating near an ice cover with hummocks of different height has been carried out. Half-wave vibrators, melted into ice at the depth of about 20 sm, were used as an antenna. Transmitted signal frequencies were from 10 to 30 MHz. A mathematical model for amplitude spatial distribution of electromagnetic wave source, placed inside an ice cover with hummocks, was developed. The results of numerical study show that, when antenna is inside hummocks, the signal is amplified. Experimental investigations show good agreement with the theoretical model.